Behavior of systemically important banks on the financial market - Buriak, Anna (Lviv Polytechnic Publishing House, 2015)
This paper investigates costs and benefits associated with systemic size of the bank for different stakeholders’ interests. Author of the research studying the behavior of systemically important banks on the financial market of Ukraine, firstly, identifies systemically important banks (first stage), secondly, analyzes behavior characteristics of these banks to find their specific features (second stage).
Keywords: behavior; systemically important banks; stakeholders; regulation; financial market